Biological Characteristics of Rhizobium Isolated from Soybean Nodules in Hanoi, Vietnam - Nguyen Kieu, Bang Tam; Phan, Thảo Thị Hồng; Nguyễn, Thu Thị Minh; Nguyễn, Hùng Quang; Nguyễn, Hiếu Văn; Nguyễn, Liên Thị Hồng (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1S, 2017)
Soybean is a high economic value crop widely grown in Vietnam and many countries in the world. This plant is capable of fixing nitrogen thanks to the activity of diverse symbiotic microorganisms. Of them, rhizobial bacteria inhabiting the roots of the legume plants play an important role in the nodulation and nitrogen fixation. In this paper, ten strains of rhizobial bacteria were isolated from root nodules of soybean grown at farms in Hanoi, and studied with respect to their physiological and biochemical characteristics. The isolate T14 was selected as the most important rhizobial bacteria for rapid in vitro growth. Taxonomic data showed that isolate T14 shared 99% similarity with species Sinorhizobium fredii , hence it was named Sinorhizobium fredii T14. Study on the physiological and cultivation characteristics of this strain revealed that the rapid growth occured within the pH range of 6 ÷ 9 and temperatures of 24 ÷ 42 o C. The strain tolerated high salt concentrations up to 2.5%. In shake flask cultures, strain T14 degraded gelatin and converted nitrate to nitrite at high rate. Fluoresence of the cultures was not observed in our study.